Real-time pen input system for writing utilizing stereo vision - Raid, Fadi Imad Osman Abu; Syed Ahmad, Sharifah Mumtazah; Hashim, Shaiful Jahari; Samsudin, Khairulmizam; Ali, Marwan (Academy Publisher, 2018)
A system that captures handwritten words on a piece of paper utilizing two cameras which observe and track a pen’s tip lateral movement is presented. The system tracks the pen’s tip in real-time based on the two images vision using colored markers. The stereo camera is calibrated for accurate threedimensional (3D) positioning of the pen’s tip. Pen’s tip 3D coordinates are then being used to re-construct the handwritten input into computer image. Experimental results show that the system can detect and track handwriting within 1mm accuracy on the y-axis and 7 mm accuracy on the x-axis (depth).